Review Paper on Academic Performance and Emotional Intelligence (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This review study explores the complex connection between academic achievement and emotional intelligence by analyzing a wide range of research studies and literature across different educational levels. The convergence of cognitive talents and emotional intelligence has gained significant recognition in recent years, as both educators and researchers acknowledge the substantial influence of emotional intelligence on academic achievement.The examination begins with a thorough discussion of the theoretical foundations of emotional intelligence and its various aspects. Following that, it thoroughly examines empirical evidence on the relationship between emotional intelligence and academic success. The findings suggest a composite association between emotional intelligence and a variety of dimensions of academic success, including grades, standardized test scores, and overall learning outcomes.Furthermore, the study looks into the impact of emotional intelligence on key academic abilities like problem-solving, critical thinking, and effective communication. The study also investigates potential moderating variables, such as gender, age, and cultural differences, that may influence the intensity and orientation of the association between emotional intelligence and academic accomplishment.An essential component of the evaluation entails analyzing interventions and instructional practices designed to improve emotional intelligence in kids and evaluating their subsequent influence on academic achievement. The paper also examines the possible mutual connection, exploring how academic experiences can impact the growth of emotional intelligence in individuals.Ultimately, this review paper highlights the complex connection between emotional intelligence and academic performance, revealing the opportunity for educators to use emotional intelligence as a catalyst for promoting comprehensive student growth and academic achievement.